Renegade Cities, Public Policy, and the Dilemmas of Federalism. - Riverstone-Newell, Lori (Lynne Rienner, 2013)
When state and federal governments intrude, abdicate responsibility, or prove unable to respond to local needs, how can cities fight back? How can they promote and defend their own interests? Addressing these questions, Lori Riverstone-Newell explores the emergence of local policy activism and its impact in a number of state and federal policy arenas.